Facile green synthesis of silver nanoparticles derived from the medicinal plant Clerodendrum serratum and its biological activity against Mycobacterium species - Vidyasagar; Ritu Raj Patel; Sudhir Kumar Singh; Deepa Dehari; Gopal Nath; Meenakshi Singh (Heliyon, 2024)
The emergence of multidrug-resistant mycobacterial strains is a significant crisis that has led to higher treatment failure rates and more toxic and expensive medications for tuberculosis (TB). The urgent need to develop novel therapeutics has galvanized research interest towards developing alternative antimicrobials such as silver nanoparticles (AgNPs). The current study focused on the anti-mycobacterial activity of green-synthesized AgNPs and its polyethylene glycol encapsulated derivative (PEG-AgNPs) with improved stability using the leaves extract of Clerodendrum serratum. Different characterization methods were used to analyze them. DLS analysis revealed a lower polydispersity index of PEG-AgNPs, suggesting a more uniform size distribution than that of AgNPs. The HR-TEM results revealed that the AgNPs and PEG-AgNPs have predominantly spherical shapes in the size range of 9–35 nm and 15–60 nm, respectively, while positive values of Zeta potential indicate their stability. FTIR-ATR analysis confirmed the presence of functional groups responsible for reducing and capping the bio-reduced AgNPs, whereas the XRD data established its crystalline nature. Impressively, the PEG-AgNPs exhibited maximum inhibitory activity against different Tubercular and Non-Tuberculous Mycobacterium species i.e., Mycobacterium smegmatis, Mycobacterium fortuitum and Mycobacterium marinum, relative to those of AgNPs and Linezolid. The flow cytometry assay showed that the anti-mycobacterial action was mediated by an increase in cell wall permeability. Notably, the results of AFM confirm their ability to inhibit mycobacterial biofilm significantly. We demonstrated the nontoxic nature of these AgNPs, explicated by the absence of hemolytic activity against human RBCs. Overall, the results suggest that PEG-AgNPs could offer a novel therapeutic approach with potential anti-mycobacterial activity and can overcome the limitations of existing TB therapies.